Measurement of integrated luminosity and center-of-mass energy of data taken by BESIII at *Supported in part by National Key Basic Research Program of China (2015CB856700), National Natural Science Foundation of China (NSFC) (11235011, 11322544, 11335008, 11425524, 11635010, 11675184, 11735014), the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; the CAS Center for Excellence in Particle Physics (CCEPP); the Collaborative Innovation Center for Particles and Interactions (CICPI); Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1232201, U1332201, U1532257, U1532258), CAS (KJCX2-YW-N29, KJCX2-YW-N45), 100 Talents Program of CAS; National 1000 Talents Program of China; INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology; German Research Foundation DFG (Collaborative Research Center CRC 1044, FOR 2359), Istituto Nazionale di Fisica Nucleare, Italy; Koninklijke Nederlandse Akademie van Wetenschappen (KNAW) (530-4CDP03), Ministry of Development of Turkey (DPT2006K-120470), National Natural Science Foundation of China (NSFC) (11505010), The Swedish Resarch Council; U. S. Department of Energy (DE-FG02-05ER41374, DE-SC-0010118, DE-SC-0010504, DE-SC-0012069), U.S. National Science Foundation; University of Groningen (RuG) and the Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt; WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (November 2017) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ahmed, S.; Ai 艾, X. C. 小聪; Albayrak, O.; Albrecht, M.; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Baldini Ferroli, R.; et al.
Abstract: To study the nature of the state Y (2175), a dedicated data set of e + e − collision data was collected at the center-of-mass energy of 2.125 GeV with the BESIII detector at the BEPCII collider. By analyzing large-angle Bhabha scattering events, the integrated luminosity of this data set is determined to be 108.49±0.02±0.85 pb −1, where the first uncertainty is statistical and the second one is systematic. In addition, the center-of-mass energy of the data set is determined with radiative dimuon events to be 2126.55±0.03±0.85 MeV, where the first uncertainty is statistical and the second one is systematic.